Faktor-Faktor Yang Berhubungan Dengan Konsumsi Sayur Pada Anak Di SD Negeri 05 Simpang Tiga Kecamatan Luhak Nan Duo Kabupaten Pasaman Barat Tahun 2014 - Rima Berlian Putri, Rima; Sari, Dian (LPPM Universitas Prima Nusantara Bukittinggi, 2015)
Vegetables and fruits are a source of the best fiber with a high water content, it useful facilitate digestion. The cause of nutrition problem is the lack of nutrition including vegetable intake in children. Thesurvey resultsobtainedfromSDN05whichat least12 peopleto consume vegetables(40%).. Secretary of the Ministry of Agriculture Directorate of Horticulture, said the people of Indonesia vegetable consumption among the lowest in the world. The low consumption of vegetables in children is influenced by several factors, knowledge, attitude, related factor availability of vegetables, and education, this study aims to determine the Factors Associated With Vegetable Consumption In Children At SD N 05 Simpang Tiga subdistrict Luhak Nan Duo West Pasaman 2014.This research is analytic studies using cross sectional study design with the entire population of mothers who have children attending the elementary school as much as 439 people, random sampling method (random sampling). The collection of data is data taken from the distribution of questionnaires to the respondents. The collected data is processed by computerized using Chi-square statistical test. These results indicate that most mothers high knowledge level of 41 (50,6%), have a positive attitude 31 (38,3%), availability of vegetables 56 (69,1%) and higher education 18 (22,2%). The results of chi-square test for knowledge obtained p = 1,000, p = 0.322 attitude, availability of vegetable p = 0.878 and p = 0.928 obtained education. It means that the probability of p> .0,05. So some hypothesis is not proven, it means there is no relationship between knowledge, attitude, availability of vegetable and education with vegetable consumption in children, Suggestedthat the counseling and health education to mothers of elementary school children about the importance of nutrition and a balanced diet containing vegetables inelementaryschoolchildren.